The role of Tumour Necrosis Factor in neuroinflammation associated with Parkinson's disease and targeted therapies. (September 2022) - Amin, Ruhul; Quispe, Cristina; Docea, Anca Oana; Ydyrys, Alibek; Kulbayeva, Marzhan; Durna Daştan, Sevgi; Calina, Daniela; Sharifi-Rad, Javad
Abstract: Neurodegenerative disorders Parkinson's disease is a progressive neurodegenerative disorder associated with neuroinflammatory responses that lead to the neurodegeneration of the dopaminergic neurons. These neuroinflammatory mechanisms involve various cytokines produced by the activated glial cells. Tumour Necrosis factor α (TNF α) is one of the major mediators of the neuroinflammation associated with neurodegeneration. TNF α has a dual role of neuroprotection and neurotoxicity in the brain. The effective pathways of TNF involve various signalling pathways transduced by the receptors TNFR1 and TNFR2. Effective therapeutic strategies have been produced targeting the neurotoxic behaviour of the Tumour Necrosis Factor and the associated neurodegeneration which includes the use of Dominant Negative Tumour Necrosis Factor (DN-TNF) inhibitors like XENP 345 and XPro®1595 and peroxisome proliferator receptor gamma (PPAR-γ) agonists. Highlights: Parkinson's disease (PD) is the second most common neurodegenerative disease. TNF α is a major mediator of the neuroinflammation associated with neurodegeneration. This review focuses on TNF α in PD and its potential as a target providing novel therapeutic strategies. TNFα inhibition with widely accessible medicines may be a potential disease-modifying therapy.